A natação e o processo de inclusão das pessoas com deficiência nas academias de Bauru - Bichusky, Rachel [UNESP]; Prado Júnior, Milton Vieira do [UNESP] (My University, 2013)
The swimming is one of the most suitable activities for the stimulation of People with Desabilitie (PWD), we want it isfor the freedom of corporal action for those that possess motive limitation, as well as, for the discovery need, corporal adaptation inthe aquatic way. This way, in the academies that develop this activity it is waited we find PWD inserted in the classes. The objective ofthis study was to verify the inclusion process it is happening in the academies of swimming of the city of Bauru-SP. A field research wasdeveloped, of qualitative character and of exploratory stamp, where they were contacted the academies that taught swimming initially andthose that they were disposed to participate in the research, in a total of 10 academies. We verified that, of a total of 3105 people enrolledin the swimming classes in the academies 19 they were only PWD, in other words, 0,61%. Although the inclusion process is found in theswimming academies, this is very limited.

A natação é uma das atividades mais indicadas para a estimulação das Pessoas com Deficiência (PCD), quer seja pela liberdadede ação corporal para aquelas que possuem limitação motora, como também, pela necessidade de descoberta, adaptação corporal no meioaquático. Desta forma, nas academias que desenvolvem esta atividade é esperado encontrarmos PCD inseridas nas aulas. O objetivodeste estudo foi verificar se o processo de inclusão está ocorrendo nas academias de natação da cidade de Bauru-SP. Foi desenvolvidauma pesquisa de campo, de caráter qualitativo e de cunho exploratório, onde foram inicialmente contatadas as academias que ensinavamnatação e aquelas que se dispuseram a participar da pesquisa, num total de 10 academias. Verificamos que, de um total de 3105 pessoasinscritas nas aulas de natação nas academias apenas 19 eram PCD, ou seja, 0,61%. Embora o processo de inclusão seja encontrado nasacademias de natação, este é muito limitado.
The swimming and the process inclusion of people whit disabilities in the academies of Bauru
Keywords: People with disabilities; Swimming; Inclusion; Academies of swimming; Pessoas com deficiência; Natação; Inclusão; Academias de natação